2021
DOI: 10.21203/rs.3.rs-1046903/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maternity Care Services Utilization and Factors Associated with Institutional Delivery Among Postpartum Women in Dabat Demographic and Health Survey Site, Northwest Ethiopia: A Community Based Baseline Survey for MNCH Surveillance

Abstract: Background Maternal continuum of care is identified to have a greatest impact on maternal and child survival. However, there is a wide variation in maternal health services utilization from place to place in Ethiopia. Therefore, knowing antenatal care, labor and delivery, and postnatal care uptake has paramount importance to take interventions. Methods A community-based cross-sectional survey was conducted among 1626 postpartum women. Descriptive statistics were done to characterize the study population and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…In the same study, the authors also noted that 14 of the 35 countries had a higher prevalence than the sub-Saharan African average of 43.91% [24]. Several community-based cross-sectional studies carried out in Ethiopia give similar high prevalence, such as 56% in 2020 [25] and 30.59% in the north-west in 2021 [26] Our study has shown that women's age at the pregnancy, contraceptive use in the woman's reproductive life, socioeconomic status of the woman, and pregnancy rank were associated with SBI. Several studies [27][28][29] have also found similar results.…”
Section: Discussionmentioning
confidence: 70%
“…In the same study, the authors also noted that 14 of the 35 countries had a higher prevalence than the sub-Saharan African average of 43.91% [24]. Several community-based cross-sectional studies carried out in Ethiopia give similar high prevalence, such as 56% in 2020 [25] and 30.59% in the north-west in 2021 [26] Our study has shown that women's age at the pregnancy, contraceptive use in the woman's reproductive life, socioeconomic status of the woman, and pregnancy rank were associated with SBI. Several studies [27][28][29] have also found similar results.…”
Section: Discussionmentioning
confidence: 70%